Identifikasi Mikroplastik Jenis Polystyrene (PS) Menggunakan Metode Wet Peroxide Oxidation (WPO) - Sukma Bening Fadli; Mawardi Mawardi; Edi Nasra (MASALIQ, 2025)
Polystyrene (PS) microplastics from styrofoam waste are persistent contaminants that are difficult to degrade naturally in aquatic environments and require effective extraction methods for analysis and mitigation. This study aims to determine the optimal conditions of Fe(II) concentration and heating temperature in the Wet Peroxide Oxidation (WPO) method for extracting PS microplastics, as well as to identify their functional groups and elemental composition. The method involved treating polluted water samples using WPO solution consisting of Fe(II) as a catalyst and 30% H₂O₂ as an oxidizing agent, with Fe(II) concentrations of 0.075 M, 0.1 M, and 0.125 M, and heating temperatures of 60°C, 75°C, and 90°C. Microplastic identification was conducted using FTIR and XRF instruments. The results showed that the optimal Fe(II) concentration was 0.125 M, yielding 1.27 grams of microplastics, while the optimal temperature was 60°C, yielding 2.58 grams of microplastics. FTIR characterization confirmed the presence of characteristic PS functional groups, including C-H bending of the benzene ring at 753.22 cm⁻¹ and aliphatic C-H stretching at 2919.27 cm⁻¹, which were also detected in samples from enclosed environments. XRF analysis under optimal conditions indicated that the elemental composition of the extracted microplastics was not entirely pure due to residual contaminants. These findings confirm the effectiveness of the WPO method for extracting PS microplastics under optimized operational conditions.